Biochemical and structural investigation of sulfoacetaldehyde reductase from Klebsiella oxytoca. Issue 4 (28th February 2019) - Zhou, Yan; Wei, Yifeng; Lin, Lianyun; Xu, Tong; Ang, Ee Lui; Zhao, Huimin; Yuchi, Zhiguang; Zhang, Yan
Abstract : Sulfoacetaldehyde reductase (IsfD) is a member of the short-chain dehydrogenase/reductase (SDR) family, involved in nitrogen assimilation from aminoethylsulfonate (taurine) in certain environmental and human commensal bacteria. IsfD catalyzes the reversible NADPH-dependent reduction of sulfoacetaldehyde, which is generated by transamination of taurine, forming hydroxyethylsulfonate (isethionate) as a waste product. In the present study, the crystal structure of Klebsiella oxytoca IsfD in a ternary complex with NADPH and isethionate was solved at 2.8 Å, revealing residues important for substrate binding. IsfD forms a homotetramer in both crystal and solution states, with the C-terminal tail of each subunit interacting with the C-terminal tail of the diagonally opposite subunit, forming an antiparallel β sheet that constitutes part of the substrate-binding site. The sulfonate group of isethionate is stabilized by a hydrogen bond network formed by the residues Y148, R195, Q244 and a water molecule. In addition, F249 from the diagonal subunit restrains the conformation of Y148 to further stabilize the orientation of the sulfonate group. Mutation of any of these four residues into alanine resulted in a complete loss of catalytic activity for isethionate oxidation. Biochemical investigations of the substrate scope of IsfD, and bioinformatics analysis of IsfD homologs, suggest that IsfD is related to the promiscuous 3-hydroxyacid dehydrogenases with diverse metabolic functions.